2018
DOI: 10.1002/jcb.28045
|View full text |Cite
|
Sign up to set email alerts
|

circRNAs (hsa_circ_00156, hsa_circ _000224, and hsa_circ _000520) are novel potential biomarkers in hepatocellular carcinoma

Abstract: Circular RNAs (circRNAs) are a newly validated type of noncoding RNAs recently found to be deregulated in several human cancers. More accurate and specific noninvasive biomarkers are strongly needed for better diagnosis and prognosis of hepatocellular carcinoma (HCC). We performed a bioinformatics analysis to retrieve a novel panel of circRNAs potentially relevant to HCC. We examined their expression in the sera of 68 patients with HCC, 60 patients with chronic hepatitis C, and 36 healthy controls using quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…For instance, hsa_circ_0091579 was significantly upregulated in tumor samples and related to poorer prognosis of HCC patients [51]. A recent study showed that the hsa_circ _00520 was associated with relapse-free survival and exhibited relatively high sensitivities and specificities compared with AFP [52]. Notably, circRNAs had been proved to be a type of non-invasive diagnosis markers for human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hsa_circ_0091579 was significantly upregulated in tumor samples and related to poorer prognosis of HCC patients [51]. A recent study showed that the hsa_circ _00520 was associated with relapse-free survival and exhibited relatively high sensitivities and specificities compared with AFP [52]. Notably, circRNAs had been proved to be a type of non-invasive diagnosis markers for human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Has_circ_0090049 enhances cell proliferation and migration and suppresses cell apoptosis. Growing evidences indicate that some circRNAs, such as hsa_circ_00156 ( 73 ), hsa_circ_000224 ( 73 ), and hsa_circ_000520 ( 73 ), hsa_circ_0091579 ( 74 ), and hsa_circ_0128298 ( 75 ), are upregulated in HCC tissues or cells. But their biological functions or mechanisms of action still needed to be elucidated.…”
Section: Role Of Circrna In Hccmentioning
confidence: 99%
“…Several studies have reported abnormal expression of circ_000244, circ_104075, circ_000520, cSMARCA5, and circ_001565 in the serum/plasma of HCC and clarified the diagnostic performance of these circRNAs in HCC (110)(111)(112)(113)(114)(115). Zhang et al revealed that HCC tissues and serum circ_104075 were highly expressed as compared with the control group.…”
Section: Circular Rnasmentioning
confidence: 99%